(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Larisa D. Bednarskaya (Orel, Russian Federation) Comprehension of educational content systems in the process of teaching allows to carry out metasubject basis of FGOS in real mode, as it provides three important heuristic directions: step-by-step practical implementation of regulatory and subject UUD in the educational process, including from school to University, system integrated study of philological disciplines, including in the aspect of system development of speech, creation of optimal models of training courses, providing level personality-oriented education. Awareness of the scientific system of the subject content allows to intensify and optimize the study of systems on an adequate scientific basis and to create on this basis modern interactive communicative and active learning models. Key words: system-activity paradigm of modern education, system of content of philological cycle courses, ways of intensification of language system study, creation of communicative-activity models of education. DOI 10.23683/1995-0640-2018-4-196-205